A COMPARATIVE STUDY OF MEDIATION OF DIVORCE CASES THROUGH LITIGATION AND NON-LITIGATION IN INDONESIA - Muhammad Jamil; Erman Gani; Alfiandri Setiawan; Abdul Aziz Harahap (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2024)
This qualitative study aims to conduct a comparative study of the mediation process of divorce cases through litigation with non-litigation This study is a qualitative research with a comparative approach. Primary data sources include Peraturan Mahkamah Agung Republik Indonesia Nomor 2 Tahun 2003 tentang Prosedur Mediasi di Pengadilan, PERMA Nomor 1 Tahun 2008 tentang Prosedur Mediasi di Pengadilan dan PERMA Nomor 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan. Data collection through documentation. The results of the study concluded that there are various competitive aspects related to the mediation of divorce cases between non-litigation and litigation, including flexibility, speed, confidentiality, whether or not a lawyer needs to help, costs, whether or not the relationship can be maintained, the right holder to carry out the procedure and the content of the settlement. Thus, praxis, mediators, both non-litigation and litigation, should first provide socialization to the parties to the husband and wife in dispute.